Energy Characterization and Gasification of Biomass Derived by Hazelnut Cultivation: Analysis of Produced Syngas by Gas Chromatography. (4th November 2012) - Monarca, D.; Colantoni, A.; Cecchini, M.; Longo, L.; Vecchione, L.; Carlini, M.; Manzo, A.
Abstract : Modern agriculture is an extremely energy intensive process. However, high agricultural productivities and the growth of green revolution has been possible only by large amount of energy inputs, especially those coming from fossil fuels. These energy resources have not been able to provide an economically viable solution for agricultural applications. Biomass energy-based systems had been extensively used for transportation and on farm systems during World War II: the most common and reliable solution was wood or biomass gasification. The latter means incomplete combustion of biomass resulting in production of combustible gases which mostly consist of carbon monoxide (CO), hydrogen (H2 ) and traces of methane (CH4 ). This mixture is called syngas, which can be successfully used to run internal combustion engines (both compression and spark ignition) or as substitute for furnace oil in direct heat applications. The aim of the present paper is to help the experimentation of innovative plants for electric power production using agro-forest biomass derived by hazelnut cultivations. An additional purpose is to point out a connection among the chemical and physical properties of the outgoing syngas by biomass characterization and gas-chromatography analysis.